Ethnography and prostitution in Peru - Nencel, Lorraine (Anthropology, culture, and society., 2001)
"A feminist study of prostitution in Peru, this book interrogates the ways in which sexuality, gender and illicit behaviour have been constructed (and deconstructed) over the years. Lorraine Nencel deals with issues such as AIDS, machismo and the regulation of the sex trade. She analyses the question of whether sex workers are victims or agents of control."--Jacket